THE DETERMINATION OF THE SENSE OF COMMUNITY LEVELS OF UNIVERSITY STUDENTS IN ONLINE DISTANCE EDUCATION ENVIRONMENTS IN TERMS OF DIFFERENT VARIABLES - Gunes, Aysun; Ozen, Emin; Aykul, Mona (ANADOLU UNIV, 2024)
Online education has been implemented in Turkiye as well as in many countries of the world in recent years and is becoming more widespread day by day. Being able to take place anytime and anywhere, eliminating the limitations of time and space, and providing lifelong learning can be described as the most basic factors in the spread of online education. In addition, due to the rapid increase in the number of learners who have to take online education due to the Covid-19 global epidemic, which has affected the whole world recently, it has become an important issue for learners to acquire knowledge and skills in online distance learning environments. Also, it is necessary to determine the level of developing a sense of community in order to ensure the learners' self-expression in the relevant environments, their active participation and the continuity of the learning action. In this study, it was aimed to determine the level of sense of community of learners studying at Turkish-German University in the 2021-2022 academic year in online distance education environments in terms of different variables like gender, level of education, and their ability to use computer programs and applications.The research was carried out in the cross-sectional scanning model. The obtained data are analyzed with the help of SPSS package program. The findings are evaluated at the 95% confidence interval and at the 5% significance level. Sub-factor averages, factor correlations are examined and diagnostic statistics related to the study group are included. In addition, t-test is used for variables with two sublevels and one-way Anova is used for variables with more than two sublevels. If there is a difference in the Anova test, Post-Hoc tests are used to determine the pairwise differences. As a result, in order to make education more efficient in online learning environments, it is concluded that in order to strengthen the sense of community, learners can be given tasks that they can discuss and negotiate, learners can be made to work in groups in related environments, etc. In adddition, considering the stress, anxiety and uncertainty that learners and educators face with the global epidemic, it is thought that social presence should take priority for learning to take place. It is recommended that the study be developed by applying it to larger regions and samples.
Keywords: Online distance education; sense of community; online learning; parametric tests; LEARNERS; Education & Educational Research